Model of Mitigation: Strategies to Utilise Unique Insider Research Opportunities - Dever, Nerolie; Barnes, Lisa; Long, Warrick (International Journal of Emerging Trends in Social Sciences, 2021)
Insider research has in the past challenged researchers in terms of blurred lines, objectivity, bias confidentiality and maintaining professional working relationships. The opportunities it presents however include access to information, trust in the data collection, insider and intimate knowledge, and the ability for rich inside data collection. This paper discusses these opportunities and challenges, then makes recommendations for ten strategies to assist in data collection by an insider researcher. These strategies include communication, mixed methods, reflections, debrief, distance, confidentiality, interview technique, social network, voluntary and objectivity. The research concludes with the creation of a Model of Mitigation, which posits the ten mitigation strategies along with the four opportunities to assist insider researchers to overcome obstacles when conducting insider research, as insider research has been shown to collect rich data and enable organisations to reflect on the research findings and to implement recommendations made on an individual but organisation wide basis.